“WHO ARE YOU, WHO AM I?” Does a psychologist need philosophy to better understand the sexual abuse of minors? - Ewa Kusz (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
This article attempts to look at the issue of sexual abuse from an anthropological point of view because the attempts by various scholarly disciplines to describe and analyze the phenomenon of sexual abuse, including attempts to identify causes and effects, do not provide clear answers to the question of the nature of what happen in sexual abuse. The first steps of the analysis show the need for a philosophical reflection, and point to the directions of such a reflection which can help to understand that the harm inflicted on a young victim by sexual abuse consists in a damage at the “core of the person,” of his own subjectivity, of his own “self.” It is an “anthropological harm or damage” resulting from “becoming an object” for the abuser. It interrupts the process of becoming an autonomous subject who understand himself and is able to enter in a dialogical relationship with others. The gist of the damage of child sexual abuse remains hidden behind the tangible long-term effects. These effects are often insurmountable during the victim’s lifetime. It indicates that we are dealing with damage to “who I am” – damage to the being of a sexually abused person. So, the person harmed in this way knows neither who I am – the person who experienced this harm, nor who you are – the perpetrator who harmed him and, in a sense, who the other is in general. Understanding the “anthropological harm” inflicted by sexual abuse clearly shows the challenge of the process of transitioning from the experience of “becoming an object” to discovering and rebuilding one’s own subjectivity, one’s own self, without denying the harm. Anthropological reflection concerns also the person of the perpetrator, who turned out to be the “bearer of evil.” Here, we have questions about intentionality, about responsibility for one’s actions, but also about the whole misery of a human being who, by objectifying another person, probably reduces himself to an object. Also, in the case of the perpetrator, understanding the process of becoming a perpetrator may help in the process of his resocialization, that is, the process of restoring his experience of his being as a free person open to meeting the other “you” who must not harmed.